"News from the Republick of Letters" : Scottish students, Charles Mackie, and the United Provinces, 1650-1750 - Mijers, Esther (Studies in medieval and Reformation traditions ;, 2012)
This book is the first full-length study of Scots in the United Provinces between 1650 and 1750, showing that the Scottish-Dutch relationship provided the infrastructure, which allowed Scotland to become part of the Republic of Letters.